Penggunaan Analisis SWOT dan Uji Litmus dalam Menentukan Strategi Pengelolaan Modal untuk Peningkatan Produksi UMKM Ina Konveksi - Nurhayati, Nurhayati; Kristianti, Ika; Permatasari, Carolina Lita (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The research aims to evaluate business capital management strategies to increase production of MSME. This descriptive qualitative research uses a case study on Ina Konveksi, with the SWOT analysis and litmus test method. The analysis results identified nine main strategies, namely: (1) attending various online and offline marketing training; (2) attend various skills and expertise training in financial bookkeeping and sales; (3) preparation and training in the use of marketing technology; (4) establishing a place for coordination and sharing between convection entrepreneurs; (5) attend a low interest credit program to increase capital; (6) establishing good cooperation with good, affordable and trusted fabric suppliers; (7) attend assistance programs from the Regional Government and Provincial Government in the field of financing creative economy businesses; (8) delivery of important information such as training programs for the use of technology, marketing and bookkeeping; and, (9) making mutually beneficial agreements between convection entrepreneurs.